EFFECTS OF THE IONOSPHERIC CONDUCTIVITY ON THE LONGITUDINAL STRUCTURE OF THE F-REGION EQUATORIAL ANOMALY - AYDOGDU, M (Pergamon-Elsevier Science Ltd, 1992)
A longitudinal comparison has been undertaken of the vertical ion velocities in terms of ion mobilities and the eastward electrojet currents in terms of the electric conductivities overhead the magnetic equator at African and West Asian regions to search for longitudinal differences in the developments of the equatorial anamoly. It is shown that the vertical ion velocities and electrojet currents in both regions are different. It is proposed that longitudinal differences in (k1i2 + k2i2)/k2i and k1i/k2i ratios give rise to a different vertical ion velocities in these regions. This is likely to cause different equatorial F-layer plasma fountain magnitudes resulting in different developments of the equatorial anomaly.
Keywords: American